2020
DOI: 10.1111/bjir.12536
|View full text |Cite
|
Sign up to set email alerts
|

How Job Changes Affect People's Lives — Evidence from Subjective Well‐Being Data

Abstract: Starting a new job is able to boost people's careers, but might come at the expense of other areas of life. To investigate individual implications of job mobility, we analyse the effects of job changes on time-use and indicators of subjective wellbeing using rich data from a representative German panel survey. We find that job switchers report relatively high levels of life satisfaction, at least for the first time after the job change. There is no such 'honeymoon' period for job changes triggered by plant clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 117 publications
2
14
1
Order By: Relevance
“…We examined employee well-being outcomes (job and life satisfaction, and sleep disturbances) after work changes and explored whether these outcomes depended on employee age and maladaptive coping expectations. In line with prior research (Chadi and Hetschko 2018 , 2021 ), we found that voluntary job changes were related to greater job satisfaction. Although voluntary job changes were also associated with life satisfaction when analyzed across employees, we could not confirm this relationship when analyzed at the within-person level.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We examined employee well-being outcomes (job and life satisfaction, and sleep disturbances) after work changes and explored whether these outcomes depended on employee age and maladaptive coping expectations. In line with prior research (Chadi and Hetschko 2018 , 2021 ), we found that voluntary job changes were related to greater job satisfaction. Although voluntary job changes were also associated with life satisfaction when analyzed across employees, we could not confirm this relationship when analyzed at the within-person level.…”
Section: Discussionsupporting
confidence: 92%
“…When studying the consequences of job changes on employee well-being, it is important to distinguish between voluntary and involuntary job changes (Garthe and Hasselhorn 2021 ). Voluntary job changes are associated with employees’ need for self-development, job improvement and career opportunities and, therefore, tend to lead to positive employee outcomes, such as higher job and life satisfaction (Chadi and Hetschko 2018 , 2021 ). Involuntary job changes are associated with organizational reorganization, downsizing, and layoffs, which may lead to lower employee well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of possible reasons were identified in the literature review (section 2) and, of these, the following remain to be investigated: a subjective feeling of not being good enough to get a permanent job; general insecurity; 18 These results are also unaffected by controlling for whether the individual has a new job, which is more likely to be the case for temps than permanent staff and has been demonstrated to provide a boost in job satisfaction (Chadi and Hetschko 2016). Analysis with this sample suggests that this boost is much more prevalent for job satisfaction than life satisfaction and should be explicitly controlled for in job satisfaction work investigating temporary employment, though see Chadi and Hetschko (2020) for recent evidence regarding the honeymoon effect of new jobs on life satisfaction.…”
Section: Section 5: Discussion Conclusion and Future Directionsmentioning
confidence: 83%
“…Second, while we justified our choice of job quality indicator, wages remain just one of many. We believe that psycho‐social markers of job control or subjective wellbeing are the next logical research frontier, as evidenced by a recent spate of empirical work in this space (e.g., Bessa et al, 2021; Chadi & Hetschko, 2021). Third, we intentionally chose to test our theory in a single country (arguably) falling under a well‐defined industrial relations “system.” An immediate next step would be to replicate this study on other national variants of the so‐called Anglo‐Saxon model.…”
Section: Discussionmentioning
confidence: 99%